(untitled) (Palíndromo, 2016)
This paper presents issues related to writing my doctoral dissertation. From the basic requirements to write until the main focus of the research, through the exercise of analyzing the work of other researchers and the possible links with my dissertation project. It also brings a brief presentation of Aloisio Magalhães - graphic design precursor in Brazil - addressing one of its facets less known (recognized): visual artist. Through its Cartemas, Aloisio appropriated the pos- tcard to create an art accessible to all and which invite the public to interaction and engagement. Finally, how I intend to work with the Aloisio’s Cartemas in order to contribute to the daily practice of the visual arts’ teacher, through the instru- ments generated by this research.